Screening of a microbial consortium for highly simultaneous degradation of lignocellulose and chlorophenols. (August 2015) - Liang, Jiajin; Peng, Xiang; Yin, Dexing; Li, Beiyin; Wang, Dehan; Lin, Yunqin
Highlights: Microbial consortium OEM1 was screened for lignocellulose/chlorophenols degradation. Spent mushroom substrates as initial microbes source utilized for OEM1 screening. OEM1 could degrade 47.2% rice straw and chlorophenols were not detected within 7 days. Dynamic change and diversity of OEM1 in degradation process were revealed by PCR-DGGE. Proteobacteria and Bacteroidetes were the predominant bacterial groups of OEM1. Abstract: In this work, spent mushroom substrates were utilized for screening a microbial consortium with highly simultaneous degradation of lignocellulose and chlorophenols. The desired microbial consortium OEM1 was gained through successive cultivation for about 50 generations and its stability of composition was verified by denaturing gradient gel electrophoresis (DGGE) during screening process. It could degrade lignocellulose and chlorophenols at around 50% and 100%, respectively, within 7 days. The diversity analysis and the growth characteristics of OEM1 during degradation process were investigated by PCR-DGGE combined with clone and sequence. The results indicated that OEM1 consisted of 31 strains. Proteobacteria and Bacteroidetes were the predominant bacterial groups. The dynamic change of OEM1 illustrated that consortium community structure was effected by pH and substrate alteration and tended to be stable after 6 days' cultivation. Furthermore, bacteria (11 strains) and actinomycetes (2 strains) were obtained based on plate isolation and identified via 16S rDNA sequence.